Decisions by Judges, Other Court Professionals, and Laypeople That Intervene in the Functioning of Families Facing Parenting Challenges With Adolescents - Sobotka, Aleksandra (Przegląd Psychologiczny, 2025)
Purpose: The purpose of this article is to compare the decisions made by court-related professionals and laypeople regarding the degree of interference of courts and subordinate institutions in the functioning of families with upbringing problems, as well as to confront the decision-making mechanisms that guide them. The research questions concerned the extent to which the possible decisions of professionals align with the beliefs of citizens who may be affected by such decisions. The results of surveys conducted among judges (n = 44), other judicial professionals (n = 51) and laypeople (n = 55) are presented. Method: The survey was carried out using a proprietary tool developed on the basis of juvenile procedure regulations and case describing young people with upbringing problems. Participants also completed Schwartz’s Portrait Values Questionnaire (PVQ). Factor analysis identified two dimensions of interaction: judicial intervention and supportive measures. Results: The results showed that all the groups studied, judges, court professionals and laypeople, preferred supportive actions. As the severity of the child’s problems increased, the frequency with which the respondents proposed intervention activities increased as well. In addition, laypeople took a more punitive stance than experts, proposing intervention measures more often. In contrast, specialists diagnosing the family indicated the most supportive actions. Conclusion: The values included in Schwartz’s circular structure were considered constructs that explain the decisions of teenagers with behavioral problems. It turned out that in the general population, values related to the self increase the propensity to intervene; this issue is different in groups representing judicial professions, among whom this tendency was not observed. The higher the pro-social values (kindness, universalism) were declared, the lower the acceptance of interventionism and the higher the acceptance of supportive measures.